Fully relativistic approach to the theory of slow and plasma ECRF waves - Pavlov, S.S.; Castejon, F. (Вопросы атомной науки и техники, 2019)
The new exact integral form for the fully relativistic plasma dielectric tensor in the ECRF range is presented. This form is suitable for numerical applications for arbitrary wave numbers. Пропонується нова точна одномірна інтегральна форма для обчислення повністю релятивістського тензора діелектричної проникності плазми. Предлагается новая точная одномерная интегральная форма для вычисления полностью релятивистского тензора диэлектрической проницаемости плазмы.